The cat o' nine tails - Argento, Dario; Argento, Salvatore, 1914-1987; Collo, Luigi; Sacchetti, Dardano; Franciscus, James; Malden, Karl; Spaak, Catherine; Capponi, Pier Paolo; Frank, Horst, 1929-1999; Rassimov, Rada; Reggiani, Aldo; De Carolis, Cinzia; et al. (Blue Underground, 2011)
When a robbery at a research institute leads to a series of brutal murders, a blind puzzle maker and a tenacious reporter begin their own investigation of the crimes. With nine different clues to follow, they find a shocking web of twisted secrets.